The Impact of Gender on Digital Stock Trading Literacy and Capital Market Discipline: A Moderating Perspective - Nurhidayah Nurhidayah; Mohamad Bastomi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The high sensitivity of investors to stock trading activities raises concerns that more and more investors are at risk of not understanding when is the right time to sell and buy stocks. This study introduces a new approach to comprehensively examine how male and female investors in Indonesia make better and more informed decisions by utilizing their understanding in the context of the digital era, especially during bearish and bullish markets. The central role of Gender will play an important role in facilitating the relationship between digital stock trading literacy and capital market discipline. An empirical online survey with a sample of 343 respondents in Indonesia is used as valid data in this study. Using the PLS-MGA model, our findings show the moderating role of Gender significantly found that digital stock trading literacy is able to influence market discipline in male and female investor groups, although male investors show a stronger influence than female investors. Male investors who have higher levels of digital stock trading literacy tend to be more disciplined in the market, while female investors, despite having high literacy, do not show the same market discipline due to other influencing factors.